A Better Way to Learn – MaxSim. Issue 1 (January 2022) - Holden, Adam
Abstract : Introduction: For Oral and Maxillofacial Surgery (OMFS) Senior House Officers (SHOs), with no formal medical training, the first exposure to emergency scenarios will be the first time they are having to manage them, usually alone. Simulation based education (SBE) has been demonstrated to increased experience and confidence when used in medical education1, therefore an OMFS SBE course was created to facilitate this learning. Methods: The course was centred around scenarios that necessitate rapid response including sepsis, retrobulbar haemorrhage and carotid artery blowout. A questionnaire was given to assess change in confidence when managing these scenarios with a ten point numerical score. Results: Learner numbers were limited due to the COVID-19 pandemic with all ten completing both questionnaires. There was an even distribution between first and second year SHOs. Two had received simulation training before however, very limited. In all stations every learner felt an increase in confidence on average by 45% (range: 38-56%, p<0.05) on the ten-point scale. Positive feedback was also given by all. Conclusions: SBE has been shown to be invaluable method of training for clinical scenarios and needs to become common in OMFS. This course is to be expanded post Covid-19 to become available nationally, with it currently being funded by HEE for the South West Deanery.